Modelling the nexus between students’ personnel services and academic achievement in secondary schools: A Partial Least Square (PLS) approach - Hanafi, Zahyah; Suleiman, Yusuf; Taslikhan, Muhajir (2016)
This study examined the nexus between student personnel services (health, guidance and counselling, and library services) and academic achievement in secondary schools with the particular interest to know the significant impact of these services on students’ academic achievement.Students’ personnel services are regarded as the cornerstones because of its undisputed role they play in ensuring smooth implementation of the school programs. Methodologically, this study is quantitative in nature and adopted a correlation survey method. Instrument titled: Students’ Personnel Services Questionnaires (SPSQ) were adapted from the previous studies.Stratified and sampling techniques were employed to select the respondents for the study. A set of questionnaire were distributed to 235 students in selected secondary schools in Ilorin South Local Government, Kwara State. Secondary data were used to measure the academic achievement. Statistical Package for Social Science (SPSS) and Structural Equation Modelling (Smart PLS) were used to analyze the collected data.The results in this study reported the existence of a relationship between health services, guidance and counselling services, library services and students’ academic achievement.Thus, it can be concluded that when health services, guidance and counselling services and library services are well provided, it would enhance students’ academic performance.This indicates that student personnel services are an indispensable service and are very crucial to the attainment of secondary education.It is recommended that the provision of students’ services should be guided by the needs and aspirations of the schools and students concerned. Lastly, The implementation of the school programs should be given utmost priority so that it can benefit students who are the beneficiaries the services provided in the school.